Kentucky bluegrass and tall fescue growth when seeded after herbicide application - McFadden, Daniele (Kansas State University, 2021)
Weed control before seeding is often required for successful turfgrass establishment since weed interference prior to turfgrass tillering causes a reduction of cover and density. However, herbicides differ widely in the delay required after herbicide application before seeding can occur. In these experiments, postemergence herbicides used for control of broadleaf weeds, annual grasses, and nutsedge were the focus. One preemergence herbicide, dithiopyr (Dimension), was also included for comparison. In Chapter 1, herbicide effects on emergence and growth of Kentucky bluegrass (Poa pratensis) and tall fescue (Schedonorus arundinaceus) were evaluated in the field when seeding was done between 0 and 14 days after application. Seeding Kentucky bluegrass or tall fescue into plots treated with 2,4-D + MCPP + dicamba (Trimec Classic, for broadleaf weeds) or quinclorac (Drive, for control of annual grasses) had little or no effect on emergence or growth, whereas seeding into plots treated with halosulfuron-methyl (Sedgehammer, for nutsedge control) or dithiopyr inhibited growth of both species. Dithiopyr exhibited less inhibition of tall fescue when seeding was done 7 or 14 DAT compared to 0 or 3 DAT, which may have been attributed to frequent irrigation prior to seeding. To evaluate the influence of irrigation, a greenhouse experiment (Chapter 2) was done using the same herbicides to evaluate emergence and growth of tall fescue seeded after application. Overall, irrigation had no influence on the impact of herbicides on shoot or root growth in the greenhouse. Growth of tall fescue seeded into soil treated with 2,4-D + MCPP + dicamba 3 to 14 DAT was similar to that in nontreated soil; however, tall fescue root volume and dry weight was inhibited when seeded before 7 DAT of quinclorac. No tall fescue emergence occurred in soil treated with dithiopyr. Finally, the introduction of new combination products focused on broadleaf weed control, raises concerns regarding the delay in seeding required after application. Therefore, another field experiment (Chapter 3) was conducted to determine the influence of combination products used for postemergence control of broadleaf weeds on emergence and growth of tall fescue seeded between 0 and 14 days after application. Seeding between 0 to 14 days after an application of carfentrazone-ethyl + MCPP + 2,4-D + dicamba (Speedzone), fluroxypyr + halauxifen-methyl + 2,4-D (GameOn), or triclopyr + pyraflufen-ethyl + 2,4-D + dicamba (4-Speed XT) had little or no effect on tall fescue emergence and growth under the conditions evaluated in these experiments, whereas tall fescue seeded into soil treated with penoxsulam + sulfentrazone + 2,4-D + dicamba (Avenue South) was consistently lower in cover, canopy height, and NDVI ratings compared to nontreated turf. In summary, under conditions evaluated in these experiments, some herbicide labels appear to suggest a greater period of time after application than is needed prior to seeding Kentucky bluegrass and/or tall fescue. Other labels are written properly or may need modifications to address concerns that could arise from seeding too soon after application.
Keywords: Turfgrass; Seeding; Herbicide application; Tall fescue; Kentucky bluegrass